1996
DOI: 10.1177/074193259601700106
|View full text |Cite
|
Sign up to set email alerts
|

Using Self-Correction to Improve the Spelling Performance of Low-Achieving Third Graders

Abstract: THIS STUDY COMPARED THE EFFECTIVENESS OF TWO SPELLING STRATEGIES (TRADITIONAL VERSUS SELF-CORRECTION) ON THE SPELLING PERFORMANCE OF SIX LOW-ACHIEVING THIRD-GRADE STUDENTS. THIS STUDY EXTENDS THE FINDINGS BY McNEISH, HERON, AND OKYERE (1992), IN WHICH SELF-CORRECTION WAS FOUND TO BE EFFECTIVE IN IMPROVING THE SPELLING PERFORMANCE OF STUDENTS WITH LEARNING DISABILITIES. IN THE CURRENT STUDY, THE TRADITIONAL SPELLING INSTRUCTIONAL STRATEGY CONSISTED OF THE STUDENTS BEING ENGAGED IN SEVERAL DIFFERENT INSTRUCTIONA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Moreover, previous research confirmed the effects of strategy instruction that includes syllable segmentation (Butyniec-Thomas & Woloshyn, 1997;Kernaghan & Woloshyn, 1995;Paffen & Bosman, 2005) and the application of spelling rules (Butyniec-Thomas & Woloshyn, 1997;Darch et al, 2006;Hilte & Reitsma, 2011;Kemper et al, 2012;Paffen & Bosman, 2005). The positive effects of self-monitoring were also in line with previous research (Grskovic & Belfoire, 1996;McGuffin et al, 1997;McNeish et al, 1992;Morton et al, 1998;Willemen et al, 2000Willemen et al, , 2002Wirtz, Gardner, Weber, & Bullara, 1996). In the strategic-monitoring condition, these aspects were combined with metacognitive questioning of which the positive effect on spelling performance was already demonstrated by Jacobs (2004).…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, previous research confirmed the effects of strategy instruction that includes syllable segmentation (Butyniec-Thomas & Woloshyn, 1997;Kernaghan & Woloshyn, 1995;Paffen & Bosman, 2005) and the application of spelling rules (Butyniec-Thomas & Woloshyn, 1997;Darch et al, 2006;Hilte & Reitsma, 2011;Kemper et al, 2012;Paffen & Bosman, 2005). The positive effects of self-monitoring were also in line with previous research (Grskovic & Belfoire, 1996;McGuffin et al, 1997;McNeish et al, 1992;Morton et al, 1998;Willemen et al, 2000Willemen et al, , 2002Wirtz, Gardner, Weber, & Bullara, 1996). In the strategic-monitoring condition, these aspects were combined with metacognitive questioning of which the positive effect on spelling performance was already demonstrated by Jacobs (2004).…”
Section: Discussionsupporting
confidence: 74%
“…The process of self-monitoring academic performance in the Wirtz et al (1996) study provides a parallel to selfmonitoring of behavior, described earlier. Recognition of a disparity between the desired and the existing behavior is the cornerstone of any program of self-directed student behavior.…”
Section: Student-directed Instructionmentioning
confidence: 99%
“…The Wirtz et al ( 1996) study cited here is worth examining as an introduction to how student-directed skills might be developed. They implemented a student-directed intervention to improve spelling within the context of a general education class.…”
Section: Student-directed Instructionmentioning
confidence: 99%
See 2 more Smart Citations